Self-rated health (SRH), recovery from work, fatigue, and insomnia among commercial pilots concerning occupational and non-occupational factors - Fu, Xi; Du, Bingqian; Chen, Qingsong; Norbäck, Dan; Lindgren, Torsten; Janson, Christer; Runeson-Broberg, Roma (Frontiers in Public Health, 2023)
Background: This study investigates associations between self-rated health (SRH), recovery from work, fatigue, insomnia and work conditions, psychosocial work environment, lifestyle, and sense of coherence (SOC) among commercial pilots. Methods: A standardized questionnaire was sent to all pilots in an airline company, and 354 (61%) participated. Associations were analyzed by ordinal and logistic regression with mutual adjustment. Results: Totally 21.8% reported low SRH, 13.0% did not recover from work during free time, 61.9% had fatigue, and 70.6% had insomnia symptoms. High work demand was associated with poor SRH and fatigue, and low social support at work was associated with insomnia and less recovery from work. The habit of exercise and BMI were associated with SRH. The part-time pilots and co-pilots reported a better recovery from work. The female pilots and younger pilots reported less fatigue. Free hours after work and the type of airplane were associated with insomnia symptoms. A high sense of coherence was protectively associated with all health outcomes. Conclusion: The psychosocial environment at work is essential for the health of pilots, and a high sense of coherence can be protective. Occupational conditions may influencen recovery from work, fatigue, and insomnia. Moreover, exercise, being fit, working part-time, and having more free hours after employment could improve health.